مبتكرات القرآن الكريم عند ابن عاشور في تفسيره (التحرير والتنوير) - الرياحنة، فادي بن محمود (جامعة الشارقة, 2013)
جاءت هذه الدراسة) مبتكرات القرآن الكريم عند ابن عاشور في تفسيره -التحرير والتنوير- ( إسهاما متواضعا في باب الدراسات البلاغية للقرآن الكريم، إذ قام الباحث فيها بتحديد مفهوم ابن عاشور لمصطلح «مبتكرات القرآن الكريم » الذي نص عليه في مقدمة تفسيره، كما قام بدراسة وتحليل عدد من المواضيع التي نص عليها المفسر أنها من مبتكرات القرآن الكريم، وختمت بدراسة منهجه رحمه الله تعالى في تناول هذه القضية This is a study of the Qur’anic Innovations according to Ibn Ashour in his \ Exegesis Al- Tahrir and Al-Tanwir. It represents a modest contribution to \ the rhetorical studies of the Qur’an in which the researcher defines Ibn \ Ashour’s understanding of the concept of “innovations in the Quran” which \ he stated in his introduction of the exegesis book. Moreover, the researcher \ studied and analyzed a number of subjects that the exegesist affirmed as \ innovations of the Qur’an. The study concludes with an examination of \ Ibn Ashour’s methodology in discussing this issue
Keywords: بن عاشور، محمد الطاهر، ت. 1393 هـ; إعجاز القرآن; القرآن الكريم; تفاسير القرآن